Fund governance contagion: New evidence on the mutual fund governance paradox - Calluzzo, Paul; Dong, Gang Nathan (Journal of Corporate Finance, 2014)
Why is poor governance pervasive in the mutual fund industry? Researchers, practitioners and regulators have attributed this failing to a lack of director independence from fund management. This paper proposes an alternate explanation: fund governance is contagious. Fund directors act as vectors, transmitting governance attributes from their primary place of employment to the fund. Using hand-collected director employment data, the paper finds that boards dominated by directors tied to the finance industry, to shareholder unfriendly firms, and to shareholder unfriendly funds, have worse governance. Examining employment shocks, litigations and firm bankruptcies, within a quasi-experimental framework, provides causal evidence that these connections cause fund governance spillover. Overall, the results suggest that contagious governance plays a role in propagating business malpractice in the mutual fund industry.